Association of toll-like receptors in malaria susceptibility and immunopathogenesis: A meta-analysis. Issue 4 (April 2022) - Ramirez Ramirez, Aína Danaisa; de Jesus, Myrela Conceição Santos; Rossit, Júlia; Reis, Nathália Faria; Santos-Filho, Marcelo Cerilo; Sudré, Adriana Pittella; de Oliveira-Ferreira, Joseli; Baptista, Andrea Regina de Souza; Storti-Melo, Luciane Moreno; Machado, Ricardo Luiz Dantas
Abstract: Toll-like receptors (TLRs) play a key role in the induced immune response in malaria. Although the potential roles of TLRs have been described, it is necessary to elucidate which of these receptors may actually have an impact on the immunopathogenesis of the disease. This article performed a meta-analysis adhered to the PRISMA statement on TLRs studied in malaria by Plasmodium falciparum and Plasmodium vivax and its impact on susceptibility and pathogenesis during malaria. A search of the literature was undertaken in PubMed, LILACS and SciELO published until June 30th, 2020. The risk of bias was calculated using the Joanna Briggs Institute's Critical Review Checklist. Later, based on the inclusion and/or exclusion criteria, 17 out of 296 articles were harvested for this systematic review, the meta-analysis included studies incorporating 6, 747 cases and 8, 983 controls. The results showed that only TLR1, TLR9 and TLR4 receptors were associated with parasitemia, TLR2 and TLR6 were related with severity and none TLR was correlated with susceptibility. The data described here should be taken with caution, since the current evidence is limited and inconsistent. More studies are needed given that the results may change depending on the region and genetic background of the populations. Abstract : Malaria; Plasmodium falciparum ; Plasmodium vivax ; Polymorphism; TLR; Toll-like receptors.